Comparison of Intra-lesional Verapamil and Intra-lesional Triamcinolone Acetonide in Treatment of Keloid - Rubab Anjum, Tahir Hassan, Muhammad Khurram Shahzad, Naima Aliya, Zunaira Anjum, Gul-e-Rukh, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Keloid is a fibrous tissue that extends past the edges of an incision. Intralesional triamcinolone acetonide is the corticosteroid most frequently used to treat keloids. Aim: To contrast the effects of intralesional triamcinolone acetonide and intralesional verapamil in treating keloid among dermatology department patients. Study Design: Comparative clinical study. Methodology: The current study was carried out at dermatology department with enrollment of 60 individuals each in both groups. Using a 30 gauge needle connected to an insulin syringe, both groups underwent intra-lesional injections in keloids three weeks apart for a total of six sessions. After the treatment was over for three months, a follow-up was conducted. SPSS 23 was used for the data analysis. Chi-square/exact Fisher's tests with a p-value of less than 0.05 were used to compare the gender distribution, outcomes, responder, and recurrence rate between the two groups. Results: Patients in group A had a mean age of 28.1 +/- 5.4 years, while those in group B had a mean age of 29.3 +/- 4.7 years. There was insignificant difference in terms of remission between both groups with 53 (88.3%) of patients in group A and 58 (96.7%) of patients in group B. However, recurrence was seen in 2 (3.3%) of the patients in group B, compared to 6 (10%) of the patients in group A, with an insignificant p-value (0.272). Practical Implication: Due to its affordability and safety, this study aided researchers in examining the effectiveness of intra-lesional verapamil as a treatment for keloid removal. Second, it contributed to the body of knowledge in the area regarding other comparable and successful treatment choices. Conclusion: It was concluded that there was insignificant difference among both groups with respect to outcomes having p-value greater than 0.05. Key words: Keloid, Intralesional Verapamil, Triamcinolone Acetonide and Clinical Outcomes.